The Liverbirds our life in Britain's first female rock 'n' roll band - McGlory, Mary; Saunders, Sylvia; O'Brien, Lucy 1961- (Faber & Faber, 2024)
"In the early '60s, four friends from Liverpool formed a band. But this is not the 'fab four' story we know - Mary, Sylvia, Valerie and Pamela - also known as The Liverbirds - were one of the world's first all-female rock'n'roll bands. At an early gig, backstage at the Cavern Club, a young John Lennon told them that 'girls don't play guitars'. But they took that as a challenge. Despite the early scepticism, they won over tough crowds, toured stadiums, recorded two hit albums, and played with the Kinks, Rolling Stones and Chuck Berry - all in the space of just five years. Now, the two surviving members of the band tell their incredible story in full for the first time - capturing a lost era of liberation and rock'n'roll, as they thrived in the vibrant Merseybeat music scene and formed a friendship that has endured through the decades."
Keywords: The Liverbirds; Liverbirds (Musical group); Women rock musicians / England / Liverpool / Biography; Rock music / England / Liverpool / History / 20th century; Rock (Musique) / Angleterre / Liverpool / Histoire / 20e siècle; Biography